Health care and doctor-patient relations in satirical and humorous interpretations of the magazine “Kolce” (1871–1914) - Napierała, Anita (Laughter, humour, satire, 2024)
The changes that took place in the second half of the 19th century in the Polish lands in the area of health care, related to its, increasing accessibility, popularization of medical and preventive knowledge, gradually increased public confidence in medicine and its representatives. On the other hand, there was a growing criticism that focused on various infirmities and flaws in the health care of the time. One form of this criticism was humor and satire presented in satirical magazines. In the form appropriate to this genre of journalism, the “realities” of medical care were presented, while at the same time creating – in a distorting mirror – the image of the doctor of the 19th century. The article discusses the above-mentioned issues in the context of medical humor contained in the humorous-satirical magazine “Kolce,” which was published in Warsaw in 1871–1914 and was among of the most popular magazines of its kind. The image of health care, including doctors and their relations with patients, created in “Kolce”, although to some extent based on stereotypical and schematic depictions, shows interesting social aspects of the functioning of health care in the second half of the 19th century.